Morality of politics / edited by Bhikhu Parekh and R. N. Berki - "Parekh, Bhikhu.(ed.) 2. Berki, R. N. (ed.)" (New York, 1972)
The (im)morality of politics is an inescapable issue for philosophers, politicians, and common citizens. It is particularly pressing in times like ours, when dramatic developments put under severe strain moral constraints on political action, while our trust in politicians is sorely tried by their words and actions. This book is a timely contribution from prominent philosophers to the public debate, exploring the fundamental problem of the relationship of politics and morality and a string of specific issues: Should political morality be more permissive of deception, manipulation, and violence? How to judge politicians who have compromised themselves on our behalf